PRAKTEK PRODUKSI HEGEMONI MILITER MELALUI FILM “JENDERAL SOEDIRMAN” - Cosmas Gatot Haryono (Universitas Bunda Mulia, 2017)
As a mass media, Film seldom unrecognized as a media disseminator for messages and discourse. This condition is used by filmmakers and some interested parties as “arena” to disseminate or conduct hegemony to the public. Film General Soedirman is one example of a film that we can felt the hegemony agenda. As a historical film, the film try to build its story or narrative centrally on the figure of the Great Commander General Soedirman. Interestingly, the protrusion of General Soedirman figure is felt too much. On the contrary, the civil politicians are discribed ugly. This led to controversy and debate that is quite exciting in the national media. There is a suspicion of a large discourse, that is being rolled out by the filmmakers for the sake of a certain position within the larger narrative of the republic.This article is a report of qualitative research and use critical discourse analysis of Van Dijk. The research try to dismantle the structure of the text, either micro, macro, and it‟s superstructure, thus unfolding discourse developed through the production of this film.Keywords: Critical Discourse, Text Structure, and Hegemony